Plath’s Spanish poems and tropes: Turning landscape into mindscape - Pascual Garrido, María Luisa (International Journal of English Studies, 2018)
Although critical attention has focused on Ariel, Sylvia Plath’s earlier poems are also worth examining since they reveal significant details concerning the writer’s evolution towards that final achievement. After getting married in June 1956, Plath and Hughes travelled to Spain and settled in Benidorm for their honeymoon. It is the poems derived from that period and Plath’s response to the alien setting that are analyzed in this paper. The corpus of “Spanish poems” and its most salient motifs will be identified and examined to assess the emotional and artistic response of Plath’s encounter with Spain in her work. A rhetorical analysis of these poems will be carried out but biographical data from Plath’s journals, correspondence and prose will also be considered. Finally, two later poems will be examined to demonstrate that Spain left its imprint in Plath’s mind, supplying suggestive imagery which turned the Spanish landscape into a violent mindscape.